Natural disasters and indigenous displacement in Bolivia - Girard, L (Refugee Studies Centre, University of Oxford, 2012)
Those seeking to understand and address the reasons for growing numbers of displaced indigenous people in Bolivia should consider the relationship between traditional knowledge and the impacts of climate change.